Properties of Soft Cheese Supplemented with Cinnamon Extract (Cinnamomum burmannii) During Storage - Ismiarti, Ismiarti; Luthfi, Nadlirotun; Putri, Beta Novia; Tuty, Septi Setyas; Rahmah, Sava Talia (Buletin Peternakan, 2025)
An innovative milk-based functional product was developed to produce a quality and healthy animal product, such antioxidant-rich cheese. The study conducted to identify the chemical composition, lactic acid bacteria (LAB) viability, color characteristic, hardness, and stickiness cheese with cinnamon extract during storage. Material used were cow milk from UPT Ternak Perah Diponegoro University, cinnamon extract, animal rennet, and culture of Lactobacillus plantarum Kita-3 from Food and Nutrition Culture Collection (FNCC), Universitas Gadjah Mada. The research assessed experimentally using completely randomized design (CRD) with 4 treatments and 6 replications. Cheese was stored on refrigerator at 4-10°C and observed at 0, 10, and 20 days to determine titrated acididity (TA), water content (WC), free fatty acid (FFA), LAB viability, color characteristics, hardness, and stickiness. Treatments were addition of cinnamon extract 0% (P0), 3% (P1), 6% (P2), and 9% (P3). Data collected was analyzed by analysis of variance and continuing with duncan’s multiple range test. The addition of cinnamon were not affected (p>0.05) to TA and FFA at 0 day observation, WC, b*, stickiness at 0 and 20 days, and hardness at 10 days. Meanwhile, it affected significantly (p<0.01) to TA at 10 and 20 days, pH and LAB viability at all observation, WC at 10 days, FFA and hardness at 0 and 20, and stickiness at 10 days. In summary, the addition of cinnamon up to 9% could produce a good quality of cheese during storage.